Pengaruh Terapi Progressive Muscle Relaxation dalam Menurunkan Hipertensi di Wilayah Kerja Puskesmas Darussalam Kabupaten Aceh Besar - Muhammad Furqan; Urip Pratama; Ellyza Fazlylawati (Jurnal Sains dan Kesehatan, 2024)
Hypertension or high blood pressure has become a common condition among the people of Indonesia and other developing countries. This study aims to evaluate the effect of Progressive Muscle Relaxation (PMR) Therapy on reducing systolic and diastolic blood pressure in individuals with hypertension.The research employed a quasi-experimental design with a one-group pre-test-post-test approach. The study population included 1,395 individuals with hypertension, and a sample of 25 participants was selected using purposive sampling techniques. Data were analyzed using the Paired T-Test.The results showed that before therapy, the average systolic blood pressure of the respondents was 148.4 mmHg, which decreased to 127.2 mmHg after therapy, indicating a reduction of 21.2 mmHg with a p-value of 0.000. In contrast, the average diastolic blood pressure was 88.00 mmHg before therapy and slightly increased to 88.40 mmHg after therapy, showing an increase of 0.40 mmHg with a p-value of 0.558.Progressive Muscle Relaxation Therapy is effective in reducing systolic blood pressure but does not have a significant effect on diastolic blood pressure. It is recommended that the research site provides health education on non-pharmacological approaches to managing hypertension through Progressive Muscle Relaxation Therapy.